HUBzero and Pegasus: integrating scientific workflows into science gateways. (21st March 2014) - McLennan, Michael; Clark, Steven; Deelman, Ewa; Rynge, Mats; Vahi, Karan; McKenna, Frank; Kearney, Derrick; Song, Carol; Wilkins‐Diehr, Nancy; Gesing, Sandra; Kiss, Tamas
Summary In this paper, we described the benefits and the challenges of integrating existing scientific workflow technologies into science gateways. Scientific workflow managers are powerful tools for handling large computational tasks. Domain scientists find it difficult to create new workflows, so many tasks that could benefit from workflow automation are often avoided or performed by hand. Two technologies have come together to bring the benefits of workflow to the masses. The Pegasus Workflow Management System can manage workflows comprised of millions of tasks, all the while recording data about the execution and intermediate results so that the provenance of the final result is clear. The HUBzero platform for scientific collaboration provides a venue for building and delivering tools to researchers and educators. With the press of a button, these tools can launch Pegasus workflows on national computing infrastructures and bring results back for plotting and visualization. As a result, the combination of Pegasus and HUBzero is bringing high‐throughput computing to a much wider audience. Copyright © 2014 John Wiley & Sons, Ltd.